Effects of equal and unequal reinforcer duration during functional analysis. - Fisher, Wayne W.; Piazza, Cathleen C.; Chiang, Christy L. (Journal of Applied Behavior Analysis)
In the functional analysis described by Iwata, Dorsey, Slifer, Bauman, and Richman (1982/1994), reinforcer duration varied across conditions (e.g., brief attention vs. 30 s of escape); this may result in unequal exposure to the establishing operations for aberrant behavior. In this study, we compared the effects of unequal and equal reinforcer duration during a functional analysis. The results showed that reinforcer duration affects the rate of aberrant behavior and may potentially alter functional analysis interpretation. Reprinted by permission of the publisher.